A brief overview of global biotechnology. (22nd January 2021) - Martin, Donald K.; Vicente, Oscar; Beccari, Tommaso; Kellermayer, Miklós; Koller, Martin; Lal, Ratnesh; Marks, Robert S.; Marova, Ivana; Mechler, Adam; Tapaloaga, Dana; Žnidaršič-Plazl, Polona; Dundar, Munis
Abstract: Biotechnology is an innovative, interdisciplinary field that impacts many different sectors, including agriculture, veterinary, medicine, pharmaceutical and fine chemicals production. It is emerging as one of the leading technologies for the transition towards carbon-free society and for solving critical societal challenges comprising health protection, food and energy supply, and environmental protection. Professional networks such as EBTNA (European Biotechnology Thematic Network Association) are important to disseminate knowledge and raise awareness of biotechnology as one of the key enabling technologies for sustainable production.